Do Financial Development and Trade Liberalization Influence Environmental Quality in Indonesia? Evidence-based on ARDL Model - Ridzuan, Abdul Rahim; Fianto, Bayu Arie; Esquivias, Miguel Angel; Kumaran, Vikniswari Vija; Shaari, Mohd Shahidan; Albani, Aliashim (International Journal of Energy Economics and Policy, 2022)
The deepening of financial development and trade liberalization has been taking place in Indonesia since the Association of Southeast Asian Countries (ASEAN) formed in 1967. As a result, Indonesia experienced substantial growth in various economic sectors. However, this growth could also bring a negative externality such as environmental degradation to this country. This research paper investigated how financial development and trade liberalization could affect the country’s environmental quality. This research utilized the time series approach, such as the Autoregressive Distributed Lag Model (ARDL), to test the determinant of environmental quality for Indonesia based on selected macroeconomic determinants with special emphasis on financial development and trade liberalization. The study used annual data from 1971 until 2020, which spans about 50 years. Based on the main outcomes, deepening financial development helps to improve environmental quality. However, at the same time, higher trade liberalization has caused greater environmental degradation. Therefore, the policymakers must ensure that more financial institutions in the country support their government in promoting sustainable growth by giving more loans to companies that promote using clean energy for development purposes. Besides, the country should monitor more closely any heavy industries such as chemicals production that operate to meet the demand for the oversea market by ensuring strict rules are enforced to avoid any negative externalities to the environment.